A Novel Synthesis of Tetrasubstituted Pyrroles via Tandem Benzylic Oxidative Cyclization - Yavari, Issa; Bayat, Mohammad J. (Synlett, 2013)
A new method for the synthesis of tetrasubstituted pyrroles from a domino reaction between primary benzylamines and dialkyl acetylenedicarboxylates, in the presence of potassium cyanide without using a metal or oxidant, is described.
Keywords: pyrrole; acetylenic ester; primary benzylamine; potassium cyanide